PENGARUH KOMPETENSI PEDAGOGIK DAN MOTIVASI TERHADAP KINERJA GURU DIMODERASI SUPERVISI AKADEMIK (Studi Kasus pada Guru SD di UPT Dinas pendidikan Kecamatan Gunem Kabupaten Rembang) - Makhsunnah, 13.52.02.0024; Suhari, Yohannes (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study was conducted to examine the effect of the variables of teacher competence pedagogik and motivation to the performance of civil service teachers in the district education office UPT Gunem with supervision as a moderating variable. The population in this study was the civil servant teachers in elementary schools-District of Gunem, as many as 113 people. Data were collected using questionnaires and the returned and processed as many as 113 . Test instruments used are validity and reliability . While model used is the coefficient of determination.Test this hypothesis using regression analysis. Based on the results of the study concluded as follows : competence and supervising positive and significant effect on performance, Â motivation of work does not affect the performance of teachers. While the results of multiple regression testing moderation model suggests that supervision is not able to moderate the effects of competenceand motivation on teacher. Keywords: competence, motivation, supervision, Performance.